Penentuan Harga Pokok Produksi Pupuk Kompos di Kul-Kul Farm PT Global Camp Bali - PUTRA, I KETUT ARY MAHENDRA; DEWI, IDA AYU LISTIA; UTARI, NI KADEK SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Determination of Cost of Compost Fertilizer Production at Kul-Kul Farm.  Determination of the cost of production is very important. However, in the manufacture of compost at Kul-Kul Farm, PT. Global Camp has not carried out the process of calculating the cost of production in detail because there are still factory overhead costs that have not been taken into account. This study is intended to identify the components of investment and operating costs, to determine the HPP calculation carried out by Kul-Kul Farm, to determine the amount of HPP compost fertilizer in the company using the full costing method, to compare the differences in HPP calculations carried out by the company and by using the full costing method. This research was conducted at Kul-Kul Farm PT. Global Camp which is located in Banjar Saren Jl. Raya Sibang Kaja, Abiansemal District, Badung Regency, Bali Province. The data used are production data from August 2019 to September 2019. The respondents used in this study were determined intentionally which included company owners and employees at Kul-Kul Farm PT. Global Camp. The results of this study are known to the company's investment costs of Rp. 147,205,000. Operating costs during the production period from August to September 2019 amounted to 8,537,700. Calculation of hpp compost using the company's method per kilogram Rp. 1,657, and HPp per unit is Rp. 99,464. HPp full costing per unit is Rp.121,967 and per kg is Rp.2,033. The difference between the company's HPP calculation method and the full costing method is IDR 376 per kilogram, and IDR 22,503 per unit.